(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2019)
The aim of this paper was quantify the effect of the herbicides clethodim and paraquat associated with different adjuvants class on phytotoxicity of Digitaria insularis at flowering stage. The herbicides were applied at 0, 6.25, 12.5, 25, 50, 75 and 100% of recommended label isolated or associated with the adjuvants: nonylphenoxy polyethoxy ethanol at 0.05%; silicone polyether copolymer at 0.1%; lecithin-based adjuvant and acid propionic at 0.5% and mineral oil at 0.5%. The experimental design were completely randomized with five replications in factorial scheme (herbicides rates x adjuvants). The phytotoxicity effect was visually assessed for paraquat at 12 days after treatment (DAT) and at 21 DAT for clethodim. The treatments applied clethodim with the adjuvants nonylphenoxy polyethoxy ethanol, lecithin-based adjuvant and acid propionic and mineral oil significantly increased the phytotoxicity of D. insularis plants. For the paraquat the increase phytotoxicity of D. insularis plants was provided by the treatment with the lecithin-based and acid propionic adjuvant.